Evaluations of entomopathogenic fungi, Metarhizium anisopliae inoculate on the treated soils towards Paederus fuscipes - Tan, Andy Fu Hao; Nagao, Hideyuki; Wan Fatma Zuharah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Rove beetle, Paederus fuscipes Curtis is a natural predator of several crop pests in the agriculture ecosystem, however, their high intrusion into human settlements caused them to become public health concern due to Paedarus dermatitis infection among humans. The entomopathogenic effectiveness of Metarhizium anisopliae Mechnikov was tested as biological control towards adults Paederus fuscipes by inoculating on soils. The mortality of P. fuscipes was observed and data were subjected to analysis using ANOVA and Kaplan-Meier method. Results show that P. fuscipes tested with the highest concentration at 1.3 × 1010 conidia/mL exhibited the shortest mean mortality time at 11.0 ± 2.5 days and survival time of 7.6 ± 0.7 days, yet the secondhighest concentration exhibited at 2.2 × 109 showed mean mortality of 18.4 ± 4.2 days and survival time of 11.9 ± 0.8 days. Log Rank (Mantel-Cox) pairwise comparison indicated the significant differences between the highest concentration of 1.3 × 1010 with the control (χ2 = 62.3, df=1 p<0.0005). Both mean mortality time and survival time of P. fuscipes showed inconsistent trends from the highest concentration of M. anisopliae towards the lowest. Pathogenicity was observed at the concentrations of 106, 109, and 1010 after performing Koch’s postulates. The results were unexpected but could indicate that M. anisopliae has the potential to be a biocontrol agent at a higher concentration.